Shaking table tests of a full‐scale flat‐bottom manufactured steel silo filled with wheat: Main results on the fixed‐base configuration. (26th October 2021) - Silvestri, Stefano; Mansour, Sulyman; Marra, Matteo; Distl, Johann; Furinghetti, Marco; Lanese, Igor; Hernández‐Montes, Enrique; Neri, Caterina; Palermo, Michele; Pavese, Alberto; Rizzo Parisi, Elisa; Sadowski, Adam Jan; et al.
Abstract: This paper reports on a series of shaking table tests on a full‐scale flat‐bottom steel silo filled with soft wheat, characterized by aspect ratio of around 0.9. The specimen was a 3.64‐m diameter and 5.50‐m high corrugated‐wall cylindrical silo. Multiple sensors were used to monitor the static and dynamic response of the filled silo system, including accelerometers and pressure cells. Numerous unidirectional dynamic tests were performed consisting of random signals, sinusoidal inputs, and both artificial and real earthquake records. The objectives of this paper are (i) to provide a general overview of the whole experimental campaign and (ii) to present selected results obtained for the fixed‐base configuration. The measured data were processed to assess the static pressures, the dynamic overpressures (related to the effective mass) and the accelerations of monitored points on the silo wall, and to identify the basic dynamic properties (fundamental frequency of vibration, damping ratio, dynamic amplification factors) of the filled silo. The main findings are discussed and compared with the predictions given by available theoretical models and code provisions. It is found that the fundamental frequency slightly decreases with increasing acceleration, while it slightly increases with increasing compaction of the granular material. For close‐to‐resonance input, the dynamic amplification (in terms of peak values of accelerations) increases along the height of the silo wall up to values of around 1.4 at the top surface of the solid content. The dynamic overpressures appear to increase with depth (differently from the EN1998‐4 expectations), and to be proportional to the acceleration.